Joseph's Personal Spirituality and Adversity Quotient Based on Genesis 37-50: A Content Analysis of Literature - Rio Janto Pardede; Yatmini Yatmini; Metboki Martinus (Analisa: Journal of Social Science and Religion, 2021)
Success is everyone's dream, but not a few people retreat and even fail because they are not ready to face the process of achieving that success. Joseph is the son who is dearest to his father, but this makes his brother hate him. Joseph is a character in the Bible, and Joseph realized that all the thoughts of his brothers, all the difficulties he experienced, were solely in God's design, and God had a good purpose in the difficulties he experienced. In a sense, Joseph's personal spirituality determines how he can have an adversity quotient so that Joseph became a tough person in facing all the challenges of his life. This study aims to analyze personal spirituality and adversity quotient. The research method used is content analysis. Research questions: what is the relationship between personal spirituality and Adversity Quotient? and to what extent can personal spirituality make someone strong in AQ? The result showed that personal spirituality and adversity quotient is related to one another. Based on the text analysis, it was found that the relationship between personal spirituality and adversity quotient on content: personal spirituality that comes from family influence, personal spirituality that comes from character, Joseph's spirituality in facing challenges (family, female, wealth and power), and personal spirituality in the knowledge of God and understanding His plan thus forming his adversity quotient.